2008
DOI: 10.1186/1471-2164-9-570
|View full text |Cite
|
Sign up to set email alerts
|

Genome plasticity of Vibrio parahaemolyticus: microevolution of the 'pandemic group'

Abstract: Background: Outbreak of V. parahaemolyticus infections occurred since 1996 was linked to a proposed clonal complex, the pandemic group. The whole genome sequence provides an unprecedented opportunity for dissecting genome plasticity and phylogeny of the populations of V. parahaemolyticus. In the present work, a whole-genome cDNA microarray was constructed to compare the genomic contents of a collection of 174 strains of V. parahaemolyticus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…S7). Such rearrangements are in agreement with the supposition that extensive genome plasticity is common in Vibrio species, particularly on C-II (40). Additionally, the V. antiquarius genome contains many perfect and approximate tandem repeats.…”
Section: Resultssupporting
confidence: 72%
“…S7). Such rearrangements are in agreement with the supposition that extensive genome plasticity is common in Vibrio species, particularly on C-II (40). Additionally, the V. antiquarius genome contains many perfect and approximate tandem repeats.…”
Section: Resultssupporting
confidence: 72%
“…Molecular analysis including ribotyping, arbitrarily primed polymerase chain reaction (AP-PCR), and pulsed-field gel electrophoresis (PFGE) revealed that O3:K6 and its serovariants exhibit a high degree of genetic similarity among each other but differ from O3:K6 strains isolated before 1996 [16][17][18]. Notably, pandemic O3:K6 isolates were shown to be generally positive for the thermostable direct hemolysin (TDH) but negative for the TDH-related hemolysin (TRH; see the section entitled "TDH and TRH toxins," later in this chapter) [19].…”
Section: Parahaemolyticusmentioning
confidence: 99%
“…To date, the so-called 'pandemic group' includes 21 serotypes, based on nearly identical genotypes and molecular profiles, referred to as serovariants of O3:K6 isolates (Nair et al, 2007). Currently, there is no unanimity in the scientific community with regard to identifying a single marker for pandemic strains and suspected V. parahaemolyticus pandemic isolates have been identified by positive group-specific PCR, based on a sequence variation in the toxRS gene (Okura et al, 2003;Han et al, 2008) and the presence of the tdh gene. Quilici et al (2005) and Martinez-Urtaza et al (2005) reported evidence that pandemic V. parahaemolyticus had migrated into Europe and has been isolated from clinical cases in France (Quilici et al, 2005), in Spain (Martinez-Urtaza et al, 2005) and in Russia during gastroenteritis outbreaks (Smolikova et al, 2001).…”
mentioning
confidence: 99%